2020
DOI: 10.1039/d0ee02315a
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-rapid uptake and the highly stable storage of methane as combustible ice

Abstract: The emergence of natural gas as a key player in the current energy landscape tenders a rare opportunity for the development of new, robust gas storage technologies. Gas hydrate or...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
122
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(124 citation statements)
references
References 34 publications
2
122
0
Order By: Relevance
“…In histidine, no furth experiments were carried out as sufficient historical data was not available. In our previous work, we compared the different amino acids at a concentration 3000 ppm to form CH4 hydrate using a rocking cell [41]. In that study, we found a to pressure drop of 5.5 bar (fresh) and 4.3 bar (memory) during isothermal cooling at P = 1 bar, T = 1 °C.…”
Section: Induction Timementioning
confidence: 95%
See 1 more Smart Citation
“…In histidine, no furth experiments were carried out as sufficient historical data was not available. In our previous work, we compared the different amino acids at a concentration 3000 ppm to form CH4 hydrate using a rocking cell [41]. In that study, we found a to pressure drop of 5.5 bar (fresh) and 4.3 bar (memory) during isothermal cooling at P = 1 bar, T = 1 °C.…”
Section: Induction Timementioning
confidence: 95%
“…Recently, studies have been performed to rapidly form CH 4 hydrate under moderate pressure and temperature conditions using a thermodynamic and kinetic promoter mixture [41]. However, the effect of these chemicals on the self-preservation tendency has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%
“… 24 High storage capacity and slow liberation of gas upon dissociation enable efficient and safe storage of fuel gas based on clathrates. 24 , 25 Nevertheless, clathrates are a major safety hazard in the oil and gas industry. Residual water present in crude oil or natural gas tends to form clathrate particles which then accumulate at the pipe surfaces and plug the flow.…”
Section: Introductionmentioning
confidence: 99%
“…Before these applications, CO 2 hydrate storage and its safe and efficient transportation are crucial steps. In order to solve this problem, plant-scale demonstration studies on hydrates are underway [21] and innovative technology (that is, the application of the self-preservation effect of hydrates) has been proposed. The so-called hydrate self-preservation effect is a phenomenon in which gas hydrates can maintain stability even at atmospheric pressure in some non-equilibrium temperature regions below the freezing point [22][23][24].…”
Section: Introductionmentioning
confidence: 99%